X-chromosome data for 12 STRs: Towards an Argentinian database of forensic haplotype frequencies. (July 2019) - García, M.G.; Catanesi, C.I.; Penacino, G.A.; Gusmão, L.; Pinto, N.
Highlights: Haplotype frequencies for the 12 X-chromosome STRs included in the Argus X-12 kit. First X-STR database of whole Argentina. First database which intends to be representative of the different regions along Argentina. Abstract: The analysis of X-chromosome STRs is useful in certain kinship cases for which autosomal markers provide insufficient statistical power. Particularly, powerful results are achieved in paternity cases with a daughter, when the alleged father is not accessible for analysis, contrarily to his unquestioned mother or daughter. However, representative haplotype frequencies for this type of markers are not available for some populations, as is the case of Argentina, which prevents the quantification of the proof in routine forensic analyses. In this work we present haplotype frequencies for the 12 X-chromosome STRs included in the Investigator Argus X-12 kit, as well as segregation data, obtained from the analysis of the genetic profiles of 457 father-daughter duos, which gave us information on 914 (unrelated) haplotypes from residents of all Argentinian provinces.